CuO immobilized paper matrices: A green catalyst for conversion of CO2 to cyclic carbonates. Issue 46 (April 2021) - Aggrawal, Sudiksha; Sharma, Ruchi; Mohanty, Paritosh
Graphical abstract: Highlights: Immobilization of CuO on paper matrices by an ultrafast (5 min) microwave method. CuO immobilized paper catalyzes the conversion of CO2 into cyclic carbonates. Excellent recyclability of the catalyst (98 % efficiency even after 7 cycles). Environmental catalyst catalyzes notorious CO2 to products of industrial importance. Abstract: Paper matrices immobilized with CuO nanoflakes (width 50−100 nm and length upto 200 nm) by an ultrafast (5 min) microwave assisted method have been used as catalyst for the conversion of CO2 and epoxides into cyclic carbonates with almost 100 % yield in 20 h at a comparatively low CO2 pressure of 4 bar. Additionally, some amount of polycarbonate is also formed. The moderate TON of 121 and excellent recyclability performance (98 % retention of the catalytic activity) even after seven catalytic cycles along with the non-detectable leaching of the CuO from the paper matrices and ease of separation of the catalyst, made the CuO immobilized paper matrices a superior catalyst. The cellulose matrices not only act as a support to immobilize the CuO nanoparticles but also acts as a co-catalyst due to the presence of ample amount of hydroxyl groups in this biodegradable natural polymer. The synergy of cellulose and CuO in the immobilized paper matrices for the formation of the products can be seen as only 7 or 40 % conversion were estimated when only paper matrices or CuO was used as the catalysts, respectively. Moreover, as substrate the paper matrices has shown great potential as the destruction and re-fabrication for five consecutive cycles could hold more than 95 % of the immobilized CuO in the paper matrices.